Psikoterapi kognitif perilaku berbasis nilai spiritual untuk meningkatkan regulasi diri residivis pembegalan - Wahyu, Agung Minto; Nurfitriana, Fia; Anugrah, Panji Galih; 'Ilmi, Achmad Miftcahul; Risky, Hanif Samsu Angga; Priyambodo, Aji Bagus (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract The prevalence of recidivist tendencies in convicts of burglary cases in Pasuruan is still high. There needs to be a special intervention to reduce the recidivism tendency. The aims of this study were 1) to explore the recidivist behavior of the robbery case in Pasuruan; 2) to develop an effective spiritual value-based cognitive behavioral psychotherapy model for prisoners of burglary cases in Pasuruan. The method used is development research with ADDIE stages (Analysis, Design, Development, Implementation, and Evaluation). The results showed that 1) the results of the exploration of recidivist behavior that were manifested in the analysis of the S-O-R-C function showed that recidivist prisoners had low self-regulation and had a lot of irrational thoughts on cognitive aspects, and had spiritual values ​​that had not been internalized; 2) the results of developing a spiritual value-based cognitive behavioral psychotherapy model in five sessions in the form of modules have been highly validated by experts and potential users. The results of the limited group trial showed differences in self-regulation of recidivist subjects before and after being given psychotherapy (p<0.05). Thus, it can be concluded that the psychotherapeutic model developed is effective in increasing the self-regulation of delinquent recidivists. Keywords: Cognitive behavioral psychotherapy; recidivist; spiritual value; self-regulation; spoliation Abstrak Prevalensi kecenderungan residivis pada narapidana kasus pembegalan di Pasuruan masih tinggi. Perlu ada intervensi khusus untuk mengurangi kecenderungan residivis tersebut. Tujuan penelitian ini adalah 1) mengeksplorasi perilaku residivis kasus pembegalan di Pasuruan; 2) mengembangkan model psikoterapi kognitif perilaku berbasis nilai spiritual yang efektif bagi narapidana kasus pembegalan di Pasuruan. Metode yang digunakan adalah penelitian pengembangan dengan tahapan ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Hasil penelitian menunjukkan bahwa 1) hasil eksplorasi perilaku residivis yang diwujudkan pada analisis fungsi S-O-R-C menunjukkan bahwa narapidana residivis memiliki regulasi diri rendah dan memiliki banyak pemikiran irasional pada aspek kognitif, serta memiliki nilai spiritual yang belum terinternalisasi; 2) hasil pengembangan model psikoterapi kognitif perilaku berbasis nilai spiritual dalam lima sesi yang berwujud modul telah tervalidasi sangat tinggi oleh ahli dan calon pengguna. Hasil uji coba kelompok terbatas menunjukkan bahwa ada perbedaan regulasi diri subjek residivis sebelum dan sesudah diberikan psikoterapi (p<0,05). Dengan demikian, dapat disimpulkan bahwa model psikoterapi yang dikembangkan efektif dalam meningkatkan regulasi diri residivis pembegalan. Kata kunci: nilai spiritual; pembegalan; psikoterapi kognitif perilaku; regulasi diri; residivis